2018
DOI: 10.2147/idr.s154457
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole achieves prompt recovery of voriconazole-induced liver injury in a case of invasive aspergillosis

Abstract: Azole antifungals have frequently been linked to the presence of hepatotoxicity, but there is scarce information on cross-toxicity between these drugs or on the possibility of using some of them when this type of toxicity occurs. We report the case of a 64-year-old man with invasive aspergillosis (IA) leading to spondylodiscitis with neurological involvement. Early management included intravenous (iv) voriconazole, which had to be interrupted after 1 week due to liver damage. Therapeutic drug monitoring (TDM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…For example, switching to anidulafungin in the setting of caspofungin‐induced liver injury in 61 patients resulted in significant reduction in LFTs . Similarly, case reports and small retrospective studies utilising PCZ after voriconazole‐induced liver toxicity showed resolution of previous liver injury with successful treatment of invasive aspergillosis . These studies suggest hepatotoxicity to one azole does not predict future tolerability with other azoles, giving rationale to support switching therapy in this setting, although more investigations are needed.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…For example, switching to anidulafungin in the setting of caspofungin‐induced liver injury in 61 patients resulted in significant reduction in LFTs . Similarly, case reports and small retrospective studies utilising PCZ after voriconazole‐induced liver toxicity showed resolution of previous liver injury with successful treatment of invasive aspergillosis . These studies suggest hepatotoxicity to one azole does not predict future tolerability with other azoles, giving rationale to support switching therapy in this setting, although more investigations are needed.…”
Section: Discussionsupporting
confidence: 62%
“…The relative incidence of severe liver toxicity is variable between antifungal agents with voriconazole and PCZ appearing to have greater incidence of Grade 3/4 increase in LFTs than fluconazole and itraconazole . Although in our patients elevated LFTs are often due to many factors, such as the hematologic disease, chemotherapy treatment or from the underlying infection, studies estimate PCZ‐associated liver injury occurs in ~5%‐10% of patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posaconazole has activity against Mucorales. 41,42,[235][236][237] Combination Antifungal Therapy Only one large scale prospective randomized study on combination therapy has been conducted. It compared voriconazole plus placebo to voriconazole plus anidulafungin.…”
Section: Eortc/msg Criteria For Severely Immunosuppressed Patientsmentioning
confidence: 99%
“…Noticeably, in patients with new-onset hepatotoxicity due to voriconazole administration for IFIs, sequential use of posaconazole seems to be safe and effective, with favorable outcomes and improvement of liver biochemistry in most of the cases [122,123,124]. Independently of the acute or chronic nature of pre-existing liver injury, no dosage adjustments are recommended for individuals with hepatic impairment treated with posaconazole [113].…”
Section: Antifungal Agentsmentioning
confidence: 99%